Oligonucleotide probes detect splicing variants in situ in Drosophila embryos. - Artero, R D (1992)
We describe a method for the in situ detection of specific splicing variants. The method is based on the use of antisense oligonucleotides designed to span splice junctions labelled with digoxigenin by terminal transferase tailing. We find that the spatial patterns of Ubx splicing variants Ia and IIa are similar in early embryos, but differ in late embryos. Variant IVa is only detected in the CNS (ps6) at stages 16 and 17. We also present evidence indicating that the first splicing event is cotranscriptional.